2022
DOI: 10.1038/s41423-022-00845-6
|View full text |Cite
|
Sign up to set email alerts
|

Histones released by NETosis enhance the infectivity of SARS-CoV-2 by bridging the spike protein subunit 2 and sialic acid on host cells

Abstract: Neutrophil extracellular traps (NETs) can capture and kill viruses, such as influenza viruses, human immunodeficiency virus (HIV), and respiratory syncytial virus (RSV), thus contributing to host defense. Contrary to our expectation, we show here that the histones released by NETosis enhance the infectivity of SARS-CoV-2, as found by using live SARS-CoV-2 and two pseudovirus systems as well as a mouse model. The histone H3 or H4 selectively binds to subunit 2 of the spike (S) protein, as shown by a biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Furthermore, NETs can trap and eliminate pathogens to protect the host against viral infection. However, we found that histones, a major component of NETs, could enhance SARS‐CoV‐2 infection 142 . Mounting evidence shows that NETosis is associated with thrombosis, which is a significant predictor of disease severity in COVID‐19 patients 143 .…”
Section: The Diseases Associated With Netosismentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, NETs can trap and eliminate pathogens to protect the host against viral infection. However, we found that histones, a major component of NETs, could enhance SARS‐CoV‐2 infection 142 . Mounting evidence shows that NETosis is associated with thrombosis, which is a significant predictor of disease severity in COVID‐19 patients 143 .…”
Section: The Diseases Associated With Netosismentioning
confidence: 70%
“…Moreover, cfDNA is linked to acute‐phase reactants and lactate dehydrogenase, as well as neutrophil count, while CitH3 is linked to platelet levels, supporting a function for NETosis in thrombosis 140 . Notably, SARS‐CoV‐2 can directly cause spontaneous NET release in vitro 141,142 …”
Section: The Diseases Associated With Netosismentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to the NADPH oxidase (NOX)/ROS-, peptidylarginine deiminase 4 (PADI4)-, and NE-dependent pathways on the activation of NETosis, RIPK3/MLKL-mediated necroptosis and GSDMD-driven pyroptosis linked the excessive inflammatory response to NETosis ( 86 89 ). Emerging evidence from the clinic severe cases of COVID-19 implicated that NETosis and NET formation/release played a central role in the pathophysiology of inflammation, coagulopathy, immunothrombosis, and even organ damage during SARS-CoV-2 infection ( 90 94 ). With the growing roles of NETosis and NETs in COVID-19 reported, targeting dysregulated NETosis and NET formation/release is a new aspect of severe COVID-19 treatment.…”
Section: Multiple Cell Death Pathways Were Induced In Sars-cov-2 Infe...mentioning
confidence: 99%